Tele-Presence-as-a-Service: Smart-Glasses Streaming for Older Adults with Reduced Mobility - Siqueira, Alexandre; Peres, Fabiana; Mauricio, Claudio; Nunes, Fatima; Teixeira, João Marcelo (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
Telepresence technologies can help reduce social isolation among older adults. However, state-of-the-art systems still rely on expensive robots or head-worn displays, which many seniors find impractical. As a result, there is a lack of understanding regarding how lightweight consumer smart glasses could address this need. The goal of this work is to explore whether consumer smart glasses can act as a lightweight "eyes-and-ears proxy," virtually transporting older adults with mobility restrictions to meaningful outdoor environments without requiring them to wear any head-mounted device. We therefore ran a two-phase mixed-methods study. Phase 1 interviewed 11 residents of a Florida elder-care facility (64–83 y) to identify the destinations they miss, perceived benefits, and ethical concerns. Phase 2 captured first-person footage of the four most-requested sites with Ray-Ban Meta glasses and conducted a pilot livestream in which an operator walked through a public park and, across three five-minute sessions, streamed the walk to four viewers (three older adults, one middle-aged co-author) who watched on an Android phone and completed the 23-item Telepresence Walk Experience Questionnaire (TWEQ-Short). Presence, media fidelity, and adoption intent all reached the ceiling (Median = 5/5), while privacy and technical anxiety remained minimal (Median = 1/5); mean mood increased by one point on a 10-point VAS. The findings indicate that asymmetric, smart-glasses telepresence is a viable "presence-as-a-service" model that delivers meaningful, hands-free outdoor experiences with virtually no setup burden for the viewer, warranting larger-scale trials to refine session length, scene richness, and adaptive streaming.